Pengaruh Dimensi Kualitas Pelayanan Terhadap KepuasanMasyarakat Pada Kantor Urusan Agama Kecamatan Trucuk Kabupaten Klaten - Krisnadi, Agus; , Dr. Triyono M.Si, Ak; , Drs. Syamsudin, MM (2015)
of tangible, reliable, responsiveness, assurance, emphaty on the satisfaction of the people in the Trucuk Subdistrict Klaten regency. This study was a survey. The data was primary data. Sample were 100 residents who use the service of the Office of Religious Affairs at Trucuk Subdistrict Klaten. Sampling techniques in this study using Random Convenience sampling. Data were obtained from questionnaires. Analysis tools used linear regression. The results of t-test showed that tangible has positive effect on people's satisfaction. Reliability has positive effect on people's satisfaction. Responsiveness has positive effect on people's satisfaction. Assurance has positive effect on people's satisfaction. Empathy has positive effect on people's satisfaction. The implications of this study explain the variables that influence on people's satisfaction needs to be improved.